Using Image Media on Reading Text to Improve Reading Comprehension of Student with Intellectual Disabilities - Wadihah, Hilyatul; Fauzi, Aminulloh (Universitas Pendidikan Indonesia (UPI), 2021)
This study aims to improve students' ability in reading comprehension. One of the media that can be used for learning is image media. Image media is a visual medium that can increase the level of communication more concretely. These images also play a role in understanding the text they read. The method used is classroom action research which is a descriptive research method with a quantitative approach. The subjects of this study consisted of 2 intellectual disabilities students in class X senior high school at Special Needs School Aditya Grahita Bandung. The results showed that the use of image media in the reading comprehension of intellectual disabilities. This is indicated by the increasing ability of students to answer questions concerning the text that is read even though the answers are not exactly the same as the text. In the learning, this study was carried out by the teacher, especially in learning Indonesian, students have increased in understanding the reading text. The use of image media in each reading text can improve reading comprehension for students with intellectual disabilities. Research is useful for students in understanding a reading that can be used as a reference for teachers in the learning process.